Sacraoxides A–G, Bioactive Cembranoids from Gum Resin of Boswellia sacra - Zhang, Bingyang; Liu, Di; Ji, Wenyue; Otsuki, Kouharu; Higai, Koji; Zhao, Feng; Li, Wei; Koike, Kazuo; Qiu, Feng (Frontiers in Chemistry, 2021)
Seven undescribed cembranoids, sacraoxides A–G (1, 3–8) were isolated from the gum resin of Boswellia sacra. Their structures were elucidated by extensive physicochemical and spectroscopic analysis, as well as ECD calculation, modified Mosher’s method and X-ray diffraction crystallography. Compounds 6 and 7 exhibited inhibitory activities on nitric oxide (NO) production induced by lipopolysaccharide in RAW264.7 cells with IC50 values of 24.9 ± 1.7 and 36.4 ± 2.9 μM.